2016
DOI: 10.1007/s00170-016-8617-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on warm deep drawing of HC420LA grade sheet material

Abstract: The use of high-strength sheet material applications in the automotive industry has become widespread due to their high strength/weight ratios. The formability, however, of these high-strength sheet materials is limited at room temperatures (RTs). In this study, the first of its kind to be conducted, experimental research was performed on the formability of HC420LA grade sheet material using the warm deep drawing (WDD) method. Temperature control is the most important parameter in WDD. In this method, a new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this regard, scientists and researchers started a tendency to various applications to reduce fossil fuel consumption in transportation. For this purpose, some of them tried to modify the vehicle design [3][4][5] such as light-material usage and geometry changes, while others tried to modify the fuels [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, scientists and researchers started a tendency to various applications to reduce fossil fuel consumption in transportation. For this purpose, some of them tried to modify the vehicle design [3][4][5] such as light-material usage and geometry changes, while others tried to modify the fuels [6].…”
Section: Introductionmentioning
confidence: 99%
“…(3) and(4) were used:Taking into account the empirical constants in Eq. (2), the values of EP i,d and EP i,w in Eqs (5). and(6) were derived.…”
mentioning
confidence: 99%
“…However, sheet metal products with a high drawing ratio that cannot be formed by conventional deep drawing processes can be formed using hydroforming methods or hot forming methods where the die set or material is heated. [9][10][11][12][13][14][15][16][17][18] To increase the formability in the hydromechanical deep drawing process-a hydroforming methodthe positive effects of pre-bulging in the opposite direction of forming on deep drawability have been experimentally and analytically proven in published literature. Lang et al investigated the effects of pre-bulging on deep drawability in the hydromechanical deep drawing process with finite element analyses and experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al stated that when bending AZ31B magnesium alloy sheet in the temperature range of 50°C–300°C, the springback decreased with increasing temperature [22]. Nuri Şen, in his studies, increased the LDR ratio of local heating and also reported that the springback decreased with increasing temperature [23, 24].…”
Section: Introductionmentioning
confidence: 99%